Dinocyst stratigraphy of the Valanginian–Aptian Rurikfjellet and Helvetiafjellet formations on Spitsbergen, Arctic Norway. (11th October 2020) - Śliwińska, Kasia K.; Jelby, Mads E.; Grundvåg, Sten-Andreas; Nøhr-Hansen, Henrik; Alsen, Peter; Olaussen, Snorre
Abstract: In order to improve the understanding of how the high northern latitudes responded to the escalating warming which led to the middle Cretaceous super greenhouse climate, more temperature proxy records from the High Arctic are needed. One of the current obstacles in obtaining such records is poor age control on the Lower Cretaceous strata in the Boreal region. Here, we provide a biostratigraphic framework for the Rurikfjellet and Helvetiafjellet formations representing the lower part of the Lower Cretaceous succession on Spitsbergen. We also attempt to date the boundary between the Agardhfjellet and the Rurikfjellet formations. This study is based on dinoflagellate cysts (dinocysts) from three onshore cores (DH1, DH2 and DH5R) and three outcrop sections (Bohemanflya, Myklegardfjellet and Ullaberget). Relatively abundant and well-preserved dinocyst assemblages from the Rurikfjellet Formation date this unit as early Valanginian – early Barremian. The dinocyst assemblages from the Helvetiafjellet Formation are significantly impoverished and are characterized by reworking, but collectively indicate a Barremian–Aptian age for this formation.